Pengaruh Kinerja Keuangan Bopo, Roa, Nom Terhadap Tingkat Bagi Hasil Deposito Mudharabah BSI Cabang Jambi Periode 2015-2021 - M Heru Ramadhani; Nazori Majid; Efni Anita (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to determine the effect of financial performance, namely BOPO, ROA, NOM on the rate of profit sharing for Mudharabah deposits at BSI, and to determine the effect of financial performance, namely BOPO, ROA, NOM simultaneously on the rate of profit sharing on Mudharabah deposits at BSI. The population in this study are all BSI Financial Statements that are still operating from 2015-2021. The method used in the sample selection is purposive sampling. Based on the data analysis which was carried out partially and simultaneously, there was a positive and significant effect on the BOPO, ROA, and NOM variables on the rate of profit sharing for Mudharabah deposits at BSI.